Radiographic signs of pathology determining removal of an impacted mandibular third molar assessed in a panoramic image or CBCT - Matzen, Louise H (Dentomaxillofac Radiol, 2017)
OBJECTIVES: To (1) compare pathological findings related to the mandibular third molar in panoramic images (PAN) and CBCT; (2) estimate the frequency of removals if pathological findings were indicative; and (3) assess factors in PAN associated with resorption and marginal bone loss at the second molar as observed in CBCT. METHODS: 379 mandibular third molars were examined with PAN and CBCT. Four observers registered resorption and marginal bone loss at the second molar and increased periodontal space at the third molar in both imaging modalities. Agreement between PAN and CBCT, frequency of removals based on pathological findings in either of the two modalities and interobserver reproducibility was calculated. Logistic regression analyses assessed factors in PAN, which could predict marginal bone loss and resorption observed in CBCT. RESULTS: Agreement between PAN and CBCT: resorption 54–74%; marginal bone loss 66–85%; and increased periodontal space 92–97%. Removals based on CBCT and PAN: 58–71% and 36–65%. Interobserver percentage accordance and kappa values ranged from 57 to 98% and 0.10–0.91 for PAN and 61–97% and 0.22–0.78 for CBCT, respectively. Mesioangulated/horizontally positioned third molars were associated with marginal bone loss [odds ratio (OR) = 7.0–31.3; p < 0.001] and resorption (OR = 2.9–35.6; p < 0.001) in CBCT. Overprojection between the third and the second molars in PAN predicted resorption observed in CBCT (OR = 5.6–21.2; p < 0.001). CONCLUSIONS: Pathology associated with the third molar is more often observed in CBCT than in PAN. More third molars would be removed if pathological findings are based on CBCT. Mesioangulated/horizontally positioned third molars overprojecting the cervical/root part of the second molar in PAN are strongly associated with pathology observed in CBCT.